Genetic divergence of parents and F2 segregation in grain Amaranths - Milan Pandey,Ram (Pontificia Universidad Católica de Chile. Facultad de Agronomía e Ingeniería Forestal, 2009)
Twenty six accessions of grain Amaranths (Amaranthus hypochondriacus), including both indigenous and exotic introductions, were evaluated in the rabi season (winter crop, November-March). Based on D² analysis, the accessions were grouped into eleven clusters. Clusters I, II, and III had seven, four, and three accessions, respectively; clusters VII, VIII, IX and X had only one accession in each case. The accession in cluster V had the greatest divergence, closely followed by those of clusters IV and I. The maximum and minimum divergences were revealed between clusters VIII and XI and between II and VIL respectively. The pattern of clustering did not show any relationship with geographic origin. In a study of pattern of F2 segregation in 25 crosses involving 10 parents distributed in six clusters, eight crosses showed high breeding potential. The parents involved in these eight potential crosses showed modérate genetic divergence.